PENGENDALIAN KEONG MAS PADI SAWAH SEBAGAI KEARIFAN LOKAL MASYARAKAT DI DESA EMPAT BALAI KECAMATAN KUOK KABUPATEN KAMPAR - Hafiz Fauzana; Nelvia Nelvia; Rusli Rustam; Arman Effendi AR; Susilawati Susilawati; Idwar Idwar; Erlida Ariani; Fetmi Silvina; Fifi Puspita; Irfandri Irfandri; Pajri Ananta Yudha; Arif Fashli Hakiki; Riska Pebrianti; Rizky Ramadhoni (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Gold snail (Pomacea canaliculata L.) is the main pest of rice plants in Empat Balai Village, Kuok District, Kampar Regency. Farmers in Empat Balai Village experience gold snail infestation every year, which has an impact on production. The purpose of community service activities is to conduct community service by counseling and controlling carp pests in rice fields by utilizing local wisdom in Empat Balai Village. The methods in this service are survey, consolidation, counseling and field practice. The counseling was held at Mushallah Miftahul Jannah in Pulau Empat Hamlet, while the field practice was at the farmer’s house and rice fields in Empat Balai Village. The material provided was about bioecology and how to control the carp snail pest. It was emphasized that the recommended control carp pests are the management of carp pests in the egg phase, because one group of eggs has 500 eggs and control is easier in the egg phase. Control in the egg phase includes making drainage or small ditches, installing bamboo stakes so that the snails lay their eggs there, and collecting the eggs once a week. In the snail phase, involves setting up attractant plant traps (gadung tuber leaf, papaya leaf, and banana leaf), kalambuai traps (kaltrap), installing of irrigated nets, utilizing ducks, and vegetable molluscicides. In addition, preventive measure was taken, such as planting older seedlings. The farmers were very enthusiastic about this activity. As a result, farmers gained additional knowledge about gold snail pests and how to control them, improve farmers skills on gold snail pests control methods by utilizing local wisdom.